The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s004240000507
|View full text |Cite
|
Sign up to set email alerts
|

Rapid activation of Na + /H + -exchange in MDCK cells by aldosterone involves MAP-kinases ERK 1/2

Abstract: The mineralocorticoid aldosterone is essential for the adequate regulation of electrolyte homeostasis, extracellular volume and blood pressure. As a steroid hormone it influences cellular functions by genomic actions. Previously it has been shown that aldosterone can activate Na+/H+-exchange (NHE) by a rapid, nongenomic mechanism. Because (1) NHE can be regulated by ERK1/2 (extracellular signal-regulated kinase) and (2) steroids have been reported to rapidly activate ERK1/2, we tested the hypothesis that activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
75
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 33 publications
11
75
0
Order By: Relevance
“…The molecular mechanisms that regulate expression of CYP11B2 and production of aldosterone in the heart in general and in HCM in particular remain to be established. Aldosterone imparts a diverse array of biological effects comprising genomic (slow) and nongenomic (rapid) components, including but not limited to changes in the intracellular calcium concentration, 36 Na ϩ /H ϩ exchanger, 37 and activation of extracellular signal-regulated kinases p22/44, 25 phospholipase C, 23 and calcineurin. 24 The present findings implicate PKD and PI3K-p110␦ as the molecular mediators of cardiac hypertrophic and profibrotic effects and provide for novel mechanisms for the actions of aldosterone.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms that regulate expression of CYP11B2 and production of aldosterone in the heart in general and in HCM in particular remain to be established. Aldosterone imparts a diverse array of biological effects comprising genomic (slow) and nongenomic (rapid) components, including but not limited to changes in the intracellular calcium concentration, 36 Na ϩ /H ϩ exchanger, 37 and activation of extracellular signal-regulated kinases p22/44, 25 phospholipase C, 23 and calcineurin. 24 The present findings implicate PKD and PI3K-p110␦ as the molecular mediators of cardiac hypertrophic and profibrotic effects and provide for novel mechanisms for the actions of aldosterone.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,18,29 Besides its well-known genomic actions, aldosterone induces rapid cellular responses by activating signaling pathways independently of genomic effects. [17][18][19][20][21][22][23][24][25][26][27][28][29] The protein tyrosine kinase c-Src is abundant in the vasculature and appears to be an important signaling molecule in VSMCs. c-Src induces activation of MAPKs (p38MAPK, c-Jun NH 2 -terminal kinase, and ERK1/2), which are associated with cell growth, apoptosis, and collagen deposition.…”
Section: Aldosterone Effects On [ 3 H]proline Incorporationmentioning
confidence: 99%
“…Aldosterone induces rapid cellular responses by modulating intracellular calcium (Ca 2ϩ ) and cAMP levels, Na ϩ /H ϩ exchanger activity, and phosphorylation of signaling molecules, including protein kinase C, epidermal growth factor receptor, and mitogen-activated protein kinases (MAPKs), including c-Jun NH 2 -terminal kinase, and extracellular signal-regulated kinases (ERKs) 1/2. [17][18][19][20][21][22][23][24][25][26][27][28] We recently demonstrated that aldosterone rapidly increases activation of p38 MAPK and NAD(P)H oxidase through c-Src-dependent pathways in vascular smooth muscle cells (VSMCs). In addition, the profibrotic action of aldosterone was dependent on c-Src-regulated p38 MAPK.…”
mentioning
confidence: 99%
“…Specifically, they showed that expression of a dominant negative p44 ERK or of the MAPK phosphatase MKP-1, or treatment with the MEK1 inhibitor PD98059 reduced activation of NHE-1 by mixtures of growth factors by about 50%. Further, it has been shown that short-term activation of ERK leads to rapid stimulation of NHE1 in multiple cell types (erythrocytes, fibroblasts, MDCK-11 cells, rabbit skeletal muscle, and cultured rat neonatal and adult ventricular cardiomyocytes) when activated by diverse stimuli including growth factors, angiotensin II, and aldosterone (Wang et al, 1997;Sabri et al, 1998;Bouboula et al, 1999;Gekle et al, 2001;Wei et al, 2001;Moor et al, 2001;Snabaitis et al, 2002). At least in some cases, the short term-stimulation of NHE1 by ERK is mediated by phosphorylation of NHE1 either by ERK itself, or by p90RSK, an ERK-regulated kinase (Takahashi et al, 1999).…”
Section: Mapk Regulates Nhe1mentioning
confidence: 99%
“…Indeed, in some cell types ERK plays a clear role in either the short or long term activation of NHE1 (Aharonovitz & Granot, 1996;Bianchini et al, 1997;Wang et al, 1997;Sabri et al, 1998;Bouaboula et al, 1999;Gekle et al, 2001). However, several groups were unable to demonstrate any role of ERK in regulation of NHE1 in a number of cell types (Gillis et al, 2001;Kang et al, 1998;Pederson et al, 2002;Garnovskaya et al, 1998;Di Sario et al, 2003).…”
mentioning
confidence: 99%